2007
DOI: 10.1080/09513590701233661
|View full text |Cite
|
Sign up to set email alerts
|

CAPN10UCSNP-43, UCSNP-19 and UCSNP-63 polymorphisms and metabolic syndrome in polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is a heterogeneous endocrine disorder with individual susceptibility determined by genetic and environmental risk factors. Recently, studies have evaluated the CAPN10 gene in PCOS patients, suggesting that different alleles may play a role in PCOS susceptibility. We performed a cross-sectional study with 88 southern Brazilian hirsute patients with PCOS or idiopathic hirsutism (IH) to assess the influence of CAPN10 genetic variants on clinical and biochemical features of metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
18
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 36 publications
4
18
1
1
Order By: Relevance
“…20 The significance of the association between SNPs/haplotypes with PCOS is underlined by the positive correlation between two adjacent SNPs -UCSNP-43, UCSNP-44, specifically with hyperandrogenemia features that are central to PCOS. 12 Wiltgen et al 26 did not find a direct association between UCSNP43, UCSNP19 and UCSNP63 and susceptibility of PCOS in Brazilian patients, similar to our study and Haddad et al, Dasgupta et al, but they found an association between higher prevalence of the UCSNP43 polymorphic allele of the CAPN10 gene and metabolic syndrome in PCOS women. In the present study, the AA genotype showed elevated values in body mass index (BMI), waist to hip ratio (WHR), homeostatic model assessment model score (HOMA), triglyceride levels and very low density lipoproteins levels, and decreased levels of high density lipoprotein levels, compared to AG and GG genotypes of PCOS and controls.…”
Section: Clinical Findingssupporting
confidence: 77%
“…20 The significance of the association between SNPs/haplotypes with PCOS is underlined by the positive correlation between two adjacent SNPs -UCSNP-43, UCSNP-44, specifically with hyperandrogenemia features that are central to PCOS. 12 Wiltgen et al 26 did not find a direct association between UCSNP43, UCSNP19 and UCSNP63 and susceptibility of PCOS in Brazilian patients, similar to our study and Haddad et al, Dasgupta et al, but they found an association between higher prevalence of the UCSNP43 polymorphic allele of the CAPN10 gene and metabolic syndrome in PCOS women. In the present study, the AA genotype showed elevated values in body mass index (BMI), waist to hip ratio (WHR), homeostatic model assessment model score (HOMA), triglyceride levels and very low density lipoproteins levels, and decreased levels of high density lipoprotein levels, compared to AG and GG genotypes of PCOS and controls.…”
Section: Clinical Findingssupporting
confidence: 77%
“…the occurrence of the relationship (p = 0.027) between SNP43 polymorphism of the calpain 10 gene and the risk of PcoS development in chilean women has been reported [14]. Similar results were obtained by other researches in a group of women in Brazil [15]. Spanish researchers observed a relationship between the occurrences of PcoS and UcSNP-44, but not UcSNP-43 polymorphism [16].…”
supporting
confidence: 77%
“…a study of British researchers demonstrated no relationship between PcoS and UcSNP-43 and UcSNP-44 [18]. there is data confirming a relationship between UcSNP-43 and an increased risk of development of type 2 diabetes and metabolic syndrome in diabetes [15,19]. a relationship between UcSNP-43 and UcSNP-44 and lipid metabolism disorders in women with PcoS without diabetes [20,21] was also reported.…”
mentioning
confidence: 62%
“…It was identified as a T2DM susceptibility locus by Horikawa et al [22] and has been shown to be related to proinsulin processing, insulin secretion and insulin resistance [23]. Potential associations between five different polymorphisms and PCOS have been investigated [5,[24][25][26][27]. Insulin receptor gene (INSR) comprises 22 exons spanning 120 kilobases on chromosome 19p13.3-p13.2 [28].…”
Section: Introductionmentioning
confidence: 98%